Spin photogalvanic effect in two-dimensional collinear antiferromagnets - Rui-Chun Xiao (Nature Portfolio, 2021)
Abstract Recent discovered two-dimensional (2D) antiferromagnetic (AFM) van der Waals quantum materials have attracted increasing interest due to the emergent exotic physical phenomena. The spintronic properties utilizing the intrinsic AFM state in 2D antiferromagnets, however, have been rarely found. Here we show that the spin photogalvanic effect (SPGE), which has been predicted in three-dimensional (3D) antiferromagnets, can intrinsically emerge in 2D antiferromagnets for promising spintronic applications. Based on the symmetry analysis of possible AFM orders in the honeycomb lattice, we conclude suitable 2D AFM candidate materials for realizing the SPGE. We choose two experimentally synthesized 2D collinear AFM materials, monolayer MnPS3, and bilayer CrCl3, as representative materials to perform first-principles calculations, and find that they support sizable SPGE. The SPGE in collinear 2D AFM materials can be utilized to generate pure spin current in a contactless and ultra-fast way.